Assessing propensity to learn from safety-related events. (January 2015) - Drupsteen, Linda; Wybo, Jean-Luc
Highlights: Proposal of leading indicators for learning as part of safety indicators. Proactive measure for learning from events. Validation of individual and organizational indicators. Application through interviews in a test company. Abstract: Most organisations aim to use experience from the past to improve safety, for instance through learning from safety-related incidents and accidents. Whether an organisation is able to learn successfully can however only be determined afterwards. So far, there are no proactive measures to assess whether an organisation will be able to learn from experience, meaning whether an organisation has the propensity to learn. In this study we aimed to develop a set of indicators for the propensity to learn as part of the leading indicators for safety. To assess the propensity to learn, the individual perception of learning from experience is measured, through a set of indicators. These indicators are validated through interviews on a French production site. This organisation showed a high propensity to learn, despite some minor weaknesses with respect to involvement of employees and sharing information. On an individual level, 17% of the employees had a very positive attitude towards each step of the learning process. The proposed indicators could support the identification of weaknesses with respect to learning on an organisational level and they could facilitate the identification of training needs of the employees. Further development and tests of the indicators are however needed to apply them on a wider scale.